Tixagevimab/cilgavimab or placebo for COVID-19 in ACTIV-2: Safety, pharmacokinetics and neutralizing and anti-drug antibodies - Rachel A. Bender Ignacio; Kara W. Chew; Carlee Moser; Judith S. Currier; Joseph J. Eron; Arzhang Cyrus Javan; Mark J. Giganti; Justin Ritz; Michael Gibbs; Hervé Tchouakam Kouekam; Mark T. Esser; Eric S. Daar; et al. (iScience)
Summary: Monoclonal antibodies have potential as rapidly developable agents for treatment and prevention of emerging viruses. The ACTIV-2 trial randomized persons with mild-moderate COVID-19 to the monoclonal antibody combination tixagevimab/cilgavimab via intramuscular injection (600 mg IM) or infusion (300 mg IV) versus placebo. We present final safety and laboratory outcomes; primary outcomes were previously reported. The analyzed IM group included 214 participants, and the IV group, 106 participants. Adverse events were not different between treatment and placebo. The half-life of both components was >90 days for IM or 75 days for IV. New anti-drug antibodies were about 3 times more likely in active vs. placebo recipients. SARS-CoV-2 neutralizing antibodies increased 157-fold at 7 days and 127-fold at 1 month (IM-treated) but were less robust in IV participants. These data can inform future development of monoclonal antibodies against SARS-CoV-2 and other viruses, even if this intervention is of low utility for contemporary SARS-CoV-2 variants.